69 Sudden death and competitive sport in arrhythmogenic cardiomyopathy: a post-mortem study of young athletes. (June 2018) - Miles, Chris; Finocchiaro, Gherardo; Westaby, Joseph; Basu, Joyee; Parry-Williams, Gemma; Ensam, Bode; Papatheodorou, Stathis; MacLachlan, Hamish; Paterson, Casey; Malhotra, Aneil; Papadakis, Michael; Sharma, Sanjay; et al.
Abstract : Background: Arrhythmogenic cardiomyopathy (ACM) is an inherited heart muscle disorder characterised by fibrofatty replacement of the ventricular myocardium. It is a leading cause of sudden cardiac death (SCD) in young athletes, where morphological appearances of the right ventricle may overlap with physiological adaptation to regular intense exercise. Purpose: Evaluation of sport classification, clinical characteristics, and pathological findings in a retrospective young SCD athletic population. Methods: Between 1994–2017, 5205 consecutive cases of SCD were referred to our national cardiac pathology centre. Hearts were examined macroscopically and microscopically by an expert cardiac pathologist. 216 cases were diagnosed with ACM, of which 98 were aged 1435. Information pertaining to circumstances of death, sporting activity, and symptoms were provided by coroners' officers and family members. Competitive sport was classified into categories detailing peak static and dynamic components. Results: In the young (14–35) ACM cohort, 35/98 individuals (36%) were participants in competitive sport, 26 (74%) of whom engaged in sports with a high dynamic component. Among young competitive athletes (YCA), 31 (89%) died during physical exertion and 25 (71%) died during competitive sport. 26 (74%) had no cardiac symptoms. Heart weight was heavier in YCAs compared to the young non-athletic ACM cohort (474.4g±84.0 vs 394.0g±94.9, p<0.001) and right ventricular (RV) diameter was increased (42.4 mm±11.2 vs 35.6 mm±12.1, p=0.04). Disease was confined to the left ventricle only in six YCAs (17%) and ten (16%) non-athletes. Conclusions: Over a third of our young cohort were competitive athletes, principally engaged in sports with a high dynamic component. Sudden death due to ACM was strongly associated with physical exertion in YCAs. Heart weight and RV dimensions were also increased, suggesting a contributory effect from cardiac adaptation to sustained exercise.